Domain switching and polarization fatigue in rhombohedral PIN‐PMN‐PT and Mn‐doped PIN‐PMN‐PT single crystals. Issue 11 (10th May 2019) - Zhou, Yaming; Li, Qiang; Zhuo, Fangping; Xu, Chao; Yan, Qingfeng; Zhang, Yiling; Chu, Xiangcheng
Abstract: Domain switching process under alternating electric field was investigated by in situ polarized light microscopy in [001]‐oriented Pb(In1/2 Nb1/2 )O3 ‐Pb(Mg1/3 Nb2/3 )O3 ‐PbTiO3 (PIN‐PMN‐PT) and Mn‐doped PIN‐PMN‐PT single crystals. Only one‐step 71° switching was confirmed in pure and Mn‐doped PIN‐PMN‐PT crystals by the formed domain walls, whose projections on the (001) plane are along 45° or 135° with respect to [010] direction. Moreover, polarization and strain loops during cyclic electric field were studied in depth as a function of switching cycles. Polarization fatigue appeared obviously above 1000 bipolar cycles in PIN‐PMN‐PT samples, while Mn‐doped PIN‐PMN‐PT samples exhibited almost fatigue‐free characteristics. By considering the thermodynamic theory, the improved fatigue resistance in Mn‐doped PIN‐PMN‐PT crystals stems from the enhanced energy barrier of domain switching. Mn modification does not affect the domain switching paths, but it can enhance the energy barrier of domain switching, leading to the improved fatigue behaviors. Our results provide a useful insight into the underlying mechanisms between the domain switching process and polarization fatigue for applying high‐performance relaxor‐ferroelectric single crystals.